2011
DOI: 10.1038/bjc.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of HOXB13 : IL17BR and molecular grade index in early-stage breast cancer patients from the Stockholm trial

Abstract: Background:A dichotomous index combining two gene expression assays, HOXB13 : IL17BR (H : I) and molecular grade index (MGI), was developed to assess risk of recurrence in breast cancer patients. The study objective was to demonstrate the prognostic utility of the combined index in early-stage breast cancer.Methods:In a blinded retrospective analysis of 588 ER-positive tamoxifen-treated and untreated breast cancer patients from the randomised prospective Stockholm trial, H : I and MGI were measured using real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(155 citation statements)
references
References 20 publications
5
147
0
3
Order By: Relevance
“…This assay has been developed from the combination of two indices: the ratio of HOXB13/IL17BR genes, which predicts distant recurrence in ER-positive patients treated with tamoxifen, and a proliferation related five gene molecular grade index, which discriminates grade 1 from grade 3 disease. The test is based on qRT-PCR using RNA from paraffin embedded tissues [75,76] . The biological roles of the genes included in most of these tests are not completely understood and it is often unclear which clinical or tumor characteristics are being measured.…”
Section: Breast Cancer Indexmentioning
confidence: 99%
“…This assay has been developed from the combination of two indices: the ratio of HOXB13/IL17BR genes, which predicts distant recurrence in ER-positive patients treated with tamoxifen, and a proliferation related five gene molecular grade index, which discriminates grade 1 from grade 3 disease. The test is based on qRT-PCR using RNA from paraffin embedded tissues [75,76] . The biological roles of the genes included in most of these tests are not completely understood and it is often unclear which clinical or tumor characteristics are being measured.…”
Section: Breast Cancer Indexmentioning
confidence: 99%
“…Given the persistent risk of recurrence beyond 5 years, there is a significant clinical unmet need for biomarkers that accurately assess the risk of recurrence across the full disease time horizon. Breast Cancer Index (BCI) is a gene expression-based biomarker that was developed using a cohort of tamoxifen-treated patients from the randomized prospective Stockholm trial and has been shown to provide an individual risk of distant breast cancer recurrence based on a continuous risk model (9). BCI was developed through the algorithmic combination of 2 previously described biomarkers, HOXB13:IL17BR ratio (H/I) and the Molecular Grade Index (MGI), and provided superior prognostic performance than either biomarker alone (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the use of two predictive gene expression indices , the HOXB13: IL17BR (H:I) and the molecular grade index (MGI) which has been found to correlate with prognosis in ERþ patients with early stage breast cancer (Jerevall et al, 2011;Ma et al, 2004). The Mammastrat test has identified additional markers predictive of outcome which can be assessed using immunohistochemistry, and therefore has the potential to be more broadly performed in hospital laboratories (Ross et al, 2008;Bartlett et al, 2010) At this time; none of these assays is clearly superior over the other by any measure evaluated including cost-effectiveness (Retel et al, 2011).…”
Section: Predicting Outcome In Erd Patientsmentioning
confidence: 99%